Tropical Foliage Cultivar Development: New Ornamental Introductions Drive Plant Markets - Richard J. Henny; Jianjun Chen (EDIS)
ENH-1093, a 3-page illustrated factsheet by R.J. Henny and J. Chen, looks at foliage cultivar development and markets through history. Includes references and a table chronicling changes in major foliage plant genera in commercial production between 1975 and 1999. Published by UF Department of Environmental Horticulture, January 2008.